Results of program for applying social support of parent with TEDA4I for children with developmental delays Health Center 9, Nakhon Ratchasima. - Wongphikun, Orathai (Health Science Journal of Nakhon Ratchasima College, 2023)
Abstract This quasi-experimental study aimed to study the results of program for applying social support of parent with TEDA4I for children with developmental delays in Health Center 9, Nakhon Ratchasima. The samples were experimental group, consisted of 30 parent and 30 children with developmental delay. They received was received program by purposive sampling for 12 week. Research tools include a social support application program for parents who attend training and apply knowledge and skills to caring for children with developmental delays. Assessments to help early childhood children with developmental problems, including: Movement aspect In the use of small muscles and intelligence Language understanding Language use and help oneself and society. Statistics used for data analysis include: percentage, mean, standard deviation and One way ANOVA with repeated measures The results of the research found that after parents who received the parental social support program together with TEDA4I 1) parents had knowledge and skills in developing and evaluating development before the training, mean 63.4 and 53.3 (SD=±48.8 and ±50.7) after training, mean 96.6 and 86.6 (SD=±18.2 and ±34.5). 2) Children between the ages of 0-5 years who have developmental delays. Those who come to receive services at Health Center 9, Nakhon Ratchasima, have developed in terms of movement. In the use of small muscles and intelligence Language understanding Language use and help oneself and society Improves with each repeated measurement. Statistically significant at the 0.01 level. Summary and recommendations: The parental social support program together with TEDA4I can promote and help children between the ages of 0-5 years have better development. Therefore, the said program can be applied as a guideline for stimulating development in the hospital context.